Decontamination Efficiency of Thermal, Photothermal, Microwave, and Steam Treatments for Biocontaminated Household Textiles - Branko Neral; Selestina Gorgieva; Manja Kurečič (Molecules, 2022)
With the outbreak of the COVID-19 pandemic, textile laundering hygiene has proved to be a fundamental measure in preventing the spread of infections. The first part of our study evaluated the decontamination efficiency of various treatments (thermal, photothermal, and microwave) for bio contaminated textiles. The effects on textile decontamination of adding saturated steam into the drum of a household textile laundering machine were investigated and evaluated in the second part of our study. The results show that the thermal treatment, conducted in a convection heating chamber, provided a slight reduction in efficiency and did not ensure the complete inactivation of Staphylococcus aureus on cotton swatches. The photothermal treatment showed higher reduction efficiency on contaminated textile samples, while the microwave treatment (at 460 W for a period of 60 s) of bio contaminated cotton swatches containing higher moisture content provided satisfactory bacterial reduction efficiency (more than 7 log steps). Additionally, the treatment of textiles in the household washing machine with the injection of saturated steam into the washing drum and a mild agitation rhythm provided at least a 7 log step reduction in S. aureus. The photothermal treatment of bio contaminated cotton textiles showed promising reduction efficiency, while the microwave treatment and the treatment with saturated steam proved to be the most effective.